Kajian Ekonomi Publik Terhadap Pengelolaan Rotan oleh KUPS Desa Gohong Sebagai Upaya Pemberdayaan Masyarakat - Fendy Hariatama; Sri Rohaetin; Rahman, Rahman; Alexandro, Rinto; Grace Evelina Buji (FKIP, Universitas Palangka Raya, 2025)
Sustainable natural resource management is an important part of community economic development, especially in areas that depend on forest products. This study examines the public economic aspects of rattan management by the Social Forestry Business Group (KUPS) in Gohong Village, Central Kalimantan, as a community empowerment effort. The purpose of this study is to understand how the rattan management model implemented is able to improve community welfare while maintaining environmental sustainability through policies taken as one of the indicators of public economy. This research uses a qualitative approach with a case study method. Data was obtained through interviews with KUPS members and the Village Forest Management Agency (LPHD), direct observation of the rattan handicraft production process, and analysis of relevant policy documents. The results of the study show that rattan management by KUPS has had a very good impact on the local economy by creating business opportunities for the community, especially for women involved in the rattan handicraft industry. The shift in livelihoods from farming to rattan craftsmanship occurred as a result of the government's ban on forest burning. The rattan products produced are not only marketed at the local level but also penetrate the national market. In addition, the sustainability of this business is strengthened by the support of international grants and forest management policies that prevent over-exploitation. This study confirms that a community-based resource management model can be an effective strategy in community economic empowerment while maintaining ecological balance